Labour absorption in Nigeria's manufacturing and agriculture - Iwunor, Charles; Ukpong, Ebebe A. (Lagos : National Manpower Board, 1996)
The publication emphasized manpower and employment issues in their various multi-sectorial dimensions. It is hoped that the analytical insights unveiled by the study will not only be of interest to policy advisors but would motivate further scholastic inquiries by interested audience.
Includes bibliographical references: p. 36.
rpm 05/09/2016
Loans
Keywords: Labour market; Agricultural labourers; Manufacturing industries; Labor demand; Nigeria